Symptoms Matter: A Symptomatic but Radiographically Elusive Ascending Aortic Dissection - Papanikolaou, Dimitra; Zafar, Mohammad A.; Tanweer, Maryam; Imran, Mahnoor; Abdelbaky, Mohamed; Ziganshin, Bulat A.; Elefteriades, John A. (International Journal of Angiology, 2019)
Symptoms attributable to a thoracic aortic aneurysm (TAA) are a separate indication for prophylactic repair, irrespective of aortic size. We present the case of a 56-year-old female with a history of a thoracic ascending aortic aneurysm (TAAA) and four other heart and arch vessel abnormalities who presented to us with chest pain radiating to her back. Computed Tomography and echocardiography showed no evidence of a dissection and revealed a maximal ascending aortic diameter of 4.2 cm. The patient subsequently underwent root-sparing ascending aortic and hemiarch replacement due to her threatening symptomatology. A focal dissection was discovered intraoperatively, resembling a similar case previously reported by our team.
Keywords: thoracic aortic aneurysm; aortic dissection; aortic operation; symptomatic aneurysm; intervention criteria; genetic testing for thoracic aortic aneurysms; MYLK